2009
DOI: 10.1007/s11307-008-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in the Rodent Brain after Acute Administration of Salvinorin A

Abstract: Purpose-Salvinorin A (SA) is a potent and highly selective kappa opioid receptor (KOR) agonist with rapid kinetics and commensurate behavioral effects; however, brain regions associated with these effects have not been determined.Procedures-Freely moving adult male rats were given SA intraperitoneally during uptake and trapping of the brain metabolic radiotracer, 18 FDG, followed by image acquisition in a dedicated animal PET system. Age-matched control animals received vehicle treatment. Animal behavior durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
(37 reference statements)
1
30
1
Order By: Relevance
“…EOM Sal B and MOM Sal B have increased binding to KOPr compared to Sal A (Munro, Duncan, Xu, Wang, Liu-Chen, Carlezon et al, 2008) and MOM Sal B has been shown to be longer acting in vivo than Sal A in hotplate and hypothermic assays in the rat (Wang 2009). In a study by Hooker (2009) EOM Sal B gave 3 fold higher levels in the brain 65 min following ip. injection, indicating slower metabolism.…”
Section: Salvinorin a Analogsmentioning
confidence: 95%
See 1 more Smart Citation
“…EOM Sal B and MOM Sal B have increased binding to KOPr compared to Sal A (Munro, Duncan, Xu, Wang, Liu-Chen, Carlezon et al, 2008) and MOM Sal B has been shown to be longer acting in vivo than Sal A in hotplate and hypothermic assays in the rat (Wang 2009). In a study by Hooker (2009) EOM Sal B gave 3 fold higher levels in the brain 65 min following ip. injection, indicating slower metabolism.…”
Section: Salvinorin a Analogsmentioning
confidence: 95%
“…Both MOM Sal B and EOM Sal B have been shown to have a longer half-life in vivo compared to Sal A (Baker et al, 2009; Wang, Chen, Xu, Lee, Ma, Rawls et al, 2008). Hooker et al (2009) compared EOM Sal B to the parent compound, Sal A and showed that EOM Sal B had increased metabolic stability and decreased plasma protein affinity are likely mechanisms for its increased duration of effects (Hooker, Patel, Kothari, & Schiffer, 2009). …”
Section: Salvinorin a Analogsmentioning
confidence: 99%
“…It was found that administration of the opioid antagonist naloxone neither reduced the concentration of [ 11 C]salvinorin A nor changed its distribution in the brain. Moreover, the metabolism of labeled salvinorin A occurred not only in the parts of the brain with high KOR density, but also in brain regions with little or no KOR presence (Hooker et al 2009). There is still a need for further studies to fully understand the mechanism of action of salvinorin A.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The size of the clusters exceeding the threshold and their corrected significance were evaluated and anatomically located using a ROI template [27] in Paxinos stereotaxic space.…”
Section: Pet Analysismentioning
confidence: 99%
“…The statistical threshold was set at p<0.005 with an extent threshold of 100 contiguous voxels. Activated clusters were evaluated and anatomically located using a ROI template [27].…”
Section: Creation Of a 3d Volume Of Autoradiography And Spm Analysismentioning
confidence: 99%